Architectural and cultural heritage as a driver of social change in rural areas: 10 years (2009–2019) of management and recovery in Huete, a town of Cuenca, Spain. (April 2022) - Quintana, Diana C.; Díaz-Puente, José M.; Gallego-Moreno, Francisco
Abstract: Suitable management and recovery of architectural and cultural heritage contribute to promote the development of rural towns. This was the case of the work done for 10 years by the Fundación Huete Futuro (the Huete Future Foundation; FHF) in the town of Huete in Cuenca (Spain). This study intended to identify the drivers of impact and the social changes that this heritage management led to. To do so, two methodological approaches were employed: Participatory Impact Pathway Analysis (PIPA) and Positive Social Change (PSC). The main obtained results corresponded to the physical restoration of buildings of historic interest for Huete and the promotion of activities of cultural interest. Moreover, the integration of and social participation in the planning and management process for recovering heritage were also promoted. This heritage management and its revaluation promoted tourist activities that favoured rural development and encouraged a change in social behaviour. The population began to perceive its heritage as a means towards empowerment and innovation. Highlights: The management of architectural and cultural heritage depends on economic resources, social and cultural factors. The diffusion of results, products and activities are key to the process of management and recovery of heritage. Building and consolidating interaction networks facilitates the recovery of architectural and cultural heritage. Engaging local population through collaborative participation promotes Positive Social Change.